Commensal bacteria‐immunity crosstalk shapes mucosal homeostasis in teleost fish - Yong‐Yao Yu; Li‐Guo Ding; Zhen‐Yu Huang; Hao‐Yue Xu; Zhen Xu (Reviews in Aquaculture, 2021)
Fish harbour complex and dynamic microbiota in their mucosal surfaces. Due to the vital role of commensal microbiota in many biological functions including growth enhancement, nutrition, development, metabolism and immune response, many scholars have begun to refer to the microbiome as an ‘extended self’. Several studies have indicated that a normal microbiota contributes to fish health, and disturbances in microbial communities may lead to secondary infections and disease. Under evolutionary selective forces, fish have developed excellent innate immune mechanisms and an adaptive immune system composed of B cells and T cells to discriminate between beneficial and opportunistic bacteria for microbiome homeostasis. Many functional studies have demonstrated the involvement of immune cells, cytokines and Igs in maintaining microbiome homeostasis, and many beneficial microbes contribute to improving the immune barrier against external threats. Additionally, many host‐derived probiotics have been empirically used in the aquaculture sector and have been demonstrated to provide effective protection against fish diseases. Although little is known about the interactions between microbiota and the mucosal immune system in fish compared to mammals, managing aquaculture system microbiota may represent a promising alternative to antibiotics for disease prevention and control. This review thus provides an updated and comprehensive summary of currently characterized microbe compositions in fish mucosal tissues. Thereafter, the current knowledge on the crosstalk between microbiota and the mucosal immune system and probiotics in application is also discussed herein, thereby providing a theoretical basis for the development of microbe‐based disease control technologies in aquaculture.